Negative differential mobility in GaAs at ultrahigh fields: Comparison between an experiment and simulations - Vainshtein, Sergey; Yuferev, Valentin; Palankovski, Vassil; Ong, Duu-Sheng; Kostamovaara, Juha (AMER INST PHYSICS, 2008)
Direct measurement of the electron velocity v(n) at an extreme electric field E is problematic due to impact ionization. The dependence v(n)(E) obtained by a Monte Carlo method can be verified, however, by comparing simulated and experimental data on superfast switching in a GaAs bipolar transistor structure, in which the switching transient is very sensitive to this dependence at high electric fields (up to 0.6 MV/cm). Such a comparison allows the conclusion to be made that the change from negative to positive differential mobility predicted earlier at E similar to 0.3 MV/cm should not happen until the electric field exceeds 0.6 MV/cm. (c) 2008 American Institute of Physics.